Anoplocaryum: A newly recorded genus of Boraginaceae from China - Hao, Jia-Chen; Fan, Ying-Xin; Zhu, Deng-Xiang; Lin, Qin-Wen (Phytotaxa, 2022)
Anoplocaryum (Boraginaceae), a small genus previously known from Russia and Mongolia, is newly recorded from China. The specimen was discovered in the rock crevices of Zhangjiakou City, Hebei province, China, and was identified as A. helenae Volot. based on both morphological and molecular data. This study updates our knowledge on the geographic distribution of the genus Anoplocaryum. Two taxonomic keys were provided to distinguish Anoplocaryum and Chinese related genera, also to index taxa in Anoplocaryum.